Economic policy strategy of UNITAB - Kerékgyártóné Mislovics, Anita (Acta Agraria Debreceniensis, 2008)
Under the leadership of the International Association of Tobacco Producers – UNITAB – there is a struggle going on for stabilizing the situation of European tobacco growers. UNITAB unites the tobacco associations and tobacco growers of all EU countries. Tobacco production ensures economic stability for more than 100 thousand small- and medium-sized farms in the rural areas of 10 EU countries. In addition, its social importance in the survival of rural communities is emphasized by the 400 thousand direct or related seasonal jobs. Within the framework of the CAP reform, the European Union is gradually changing the regulations of production. This is based on the decoupling of subsidies, which will be implemented in two phases. Between 2006 and 2009. the decoupling will be 40% and then after 2010, 50% (the other 50% will be used for restructuring within the second pillar). The question is raised, how will the second 50% be restructured to the second pillar. Between regions and how it can be ensured that this support would go to tobacco production. With its participation in the principles of the European Tobacco Charta, UNITAB targets for production under economically-balanced conditions, the production of products meeting the customer requirements, consideration of the working conditions (especially for seasonal workers) and adherence to the health regulations related to the consumption of the end product already in the production and environmental protection. They aim to ensure the survival of the sector via tobacco growing with sustainable development and high quality. To maintain the continuity, there is a need for the support of regional, national and EU authorities. Future of the sector is dependent upon adaptation of tobacco growers and upon meeting the social expectations. According to UNITAB, efforts should be made to modify the decisions so that the majority of the funding could be used by the grower. The tobacco industry has been able to effectively fight for its survival.